The effect of citric acid and ascorbyl palmitate in palm oil enriched with heme iron: A model for iron fortification in bakery products. Issue 3 (17th January 2014) - Alemán, Mercedes; Bou, Ricard; Tres, Alba; Polo, Javier; Codony, Rafael; Guardiola, Francesc
<x xml:space="preserve">Abstract</x> Iron fortification in food products is a common strategy used to prevent iron deficiency. This is important because a large proportion of the population, mainly young children and women (of childbearing age) are at risk of developing iron deficiency anemia. Certain baked goods (biscuits, cookies) are regularly consumed by children making their iron fortification an effective strategy to prevent this deficiency. Although heme iron has high bioavailability it promotes oxidation, as other iron forms. In the present study, a model consisting of a refined palm oil, enriched with heme iron, was used to optimize the dose of ascorbyl palmitate (0, 100, 200, or 400 mg/kg) and citric acid (0, 250, or 500 mg/kg) to prevent oxidation in baked products. Both antioxidants were combined using a factorial design. Iron enriched samples were heated at 220°C for 10 min to mimic typical baking conditions. Primary (peroxide value and lipid hydroperoxide content) and secondary (p‐anisidine value and hexanal content) oxidation were measured over 1 year of storage at room temperature in the darkness. Results of primary and secondary oxidation indicated that ascorbyl palmitate delays oxidation during storage. Conversely, citric acid acted as prooxidant and no synergistic effect between the two antioxidants was observed. Practical applications: The fortification of food with iron represents a potentially effective strategy to overcome iron deficiency. A heme iron ingredient was used in this study because it has higher bioavailability than that of inorganic iron. As heme iron is a dark ingredient it could be disguised in baked products that contain chocolate. The heme iron ingredient was mixed with palm oil, which is a fat widely used in bakery. Nevertheless, as with inorganic iron, heme iron induces oxidation, and affects nutritional value, organoleptic properties and the shelf‐life of fortified foods. This study demonstrates that ascorbyl palmitate could be useful to prevent such undesired changes in iron fortified baked products.